Culturable Foliar Fungal Endophytes of Mangrove Species in Bicol Region, Philippines. - Guerrero, Jonathan Jaime G.
Identification of fungi in the mangrove ecosystem is warranted because of the need to document species richness in unique ecosystems, amidst the continuous anthropogenic and climatic threats to mangrove forests and the potentials for biotechnological applications. This study aimed to identify endophytic fungi in association with mangrove species. Leaves ? devoid of discoloration, wound, physical deformation, or necrosis ? of 21 mangrove species in the Bicol region, Philippines were collected. Circular discs from each leaf were surface sterilized, plated on potato dextrose agar (PDA), and incubated for 7?14 d at room temperature. Growing fungi were transferred individually into sterile PDA slants for identification. A total of 53 endophytic fungi belonging to 15 orders and 19 families were isolated ? 75.47% ascomycetes, 20.75% basidiomycetes, and 3.77% zygomycetes. Trametes cubensis (Mont.) Sacc. and Pestalotiopsis cocculi (Guba) were the most distributed among the mangrove hosts. The mangroves Rhizophora mucronata Lam. and Lumnitzera racemosa Willd. hosted the most number of fungal endophytes with 15 and 12, respectively.